The A(3) adenosine receptor attenuates the calcium rise triggered by NMDA receptors in retinal ganglion cells - Zhang, Mei (2009)
The A(3) adenosine receptor is emerging as an important regulator of neuronal signaling, and in some situations receptor stimulation can limit excitability. As the NMDA receptor frequently contributes to neuronal excitability, this study examined whether A(3) receptor activation could alter the calcium rise accompanying NMDA receptor stimulation. Calcium levels were determined from fura-2 imaging of isolated rat retinal ganglion cells as these neurons possess both receptor types. Brief application of glutamate or NMDA led to repeatable and reversible elevations of intracellular calcium. The A(3) agonist Cl-IB-MECA reduced the response to both glutamate and NMDA. While adenosine mimicked the effect of Cl-IB-MECA, the A(3) receptor antagonist MRS 1191 impeded the block by adenosine, implicating a role for the A(3) receptor in the response to the natural agonist. The A(1) receptor antagonist DPCPX provided additional inhibition, implying a contribution from both A(1) and A(3) adenosine receptors. The novel A(3) agonist MRS 3558 (1’S,2’R,3’S,4’R,5’S)-4-(2-chloro-6-(3-chlorobenzylamino)-9H-purin-9-yl)-2,3-dihydroxy-N-methylbicyclo[3.1.0] hexane-1-carboxamide and mixed A(1)/A(3) agonist MRS 3630 (1’S,2’R,3’S,4’R,5’S)-4-(2-chloro-6-(cyclopentylamino)-9H-purin-9-yl)-2,3-dihydroxy-N-methylbicyclo [3.1.0]hexane-1-carboxamide also inhibited the calcium rise induced by NMDA. Low levels of MRS 3558 were particularly effective, with an IC(50) of 400 pM. In all cases, A(3) receptor stimulation inhibited only 30-50% of the calcium rise. In summary, stimulation of the A(3) adenosine receptor by either endogenous or synthesized agonists can limit the calcium rise accompanying NMDA receptor activation. It remains to be determined if partial block of the calcium rise by A(3) agonists can modify downstream responses to NMDA receptor stimulation.